The implementation and first insights of the French-speaking Swiss programme for monitoring self-harm (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Self-harm is a major risk factor for suicide but remains poorly documented. No data on self-harm in French-speaking Switzerland exist. To address this deficiency, the Swiss Federal Office of Public Health commissioned a specific self-harm monitoring programme. We present and discuss its implementation and first findings. METHODS Every patient aged 18–65 years presenting for self-harm to the emergency departments of the Lausanne and Neuchâtel general hospitals were included in the monitoring programme over a 10-month period (December 2016 to September 2017). Clinicians collected anonymous sociodemographic and clinical data. RESULTS The sample included 490 patients (54.9% female and 45.1% male) for 554 episodes of self-harm, showing a higher proportion of patients aged 18–34 (49.2%) than older age groups (35–49, 33.7% and 50–65, 17.1%). Patients were mostly single (56.1%) and in problematic socioeconomic situations (65.7%). Self-poisoning was the most commonly used method (58.2%) and was preferred by women (71% of females and 42.5% of males, Fisher’s exact test, p